Blood Flow Restriction Training: To Adjust or Not Adjust the Cuff Pressure Over an Intervention Period? - Cerqueira, Mikhail Santos; Costa, Eduardo Caldas; Santos Oliveira, Ricardo; Pereira, Rafael; Brito Vieira, Wouber Hérickson (Frontiers in Physiology, 2021)
Abstract Blood flow restriction (BFR) training combines exercise and partial reduction of muscular blood flow using a pressured cuff. BFR training has been used to increase strength and muscle mass in healthy and clinical populations. A major methodological concern of BFR training is blood flow restriction pressure (BFRP) delivered during an exercise bout. Although some studies increase BFRP throughout a training intervention, it is unclear whether BFRP adjustments are pivotal to maintain an adequate BFR during a training period. While neuromuscular adaptations induced by BFR are widely studied, cardiovascular changes throughout training intervention with BFR and their possible relationship with BFRP are less understood. This study aimed to discuss the need for BFRP adjustment based on cardiovascular outcomes and provide directions for future researches. We conducted a literature review and analyzed twenty-nine studies investigating cardiovascular adaptations following BFR training. Participants in the studies were healthy, middle-aged adults, older adults and clinical patients. Cuff pressure, when adjusted, was increased during the training period. However, cardiovascular outcomes did not provide a plausible rationale for cuff pressure increase. In contrast, avoiding increments in cuff pressure may minimize discomfort, pain and risks associated with BFR interventions, particularly in clinical populations. Given that cardiovascular adaptations induced by BFR training are conflicting, it is challenging to indicate whether increases or decreases in BFRP are needed. Based on the available evidence, we suggest that future studies investigate if maintaining or decreasing cuff pressure makes BFR training safer and/or more comfortable with similar physiological adaptation.